2000
DOI: 10.1046/j.1439-0434.2000.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Poaceae Potyviruses by Reverse Transcription‐Polymerase Chain Reaction and Restriction Analysis

Abstract: Four potyviruses have been reported to infect Poaceae: maize dwarf mosaic virus (MDMV), sugarcane mosaic virus (SCMV), johnsongrass mosaic virus (JGMV) and sorghum mosaic virus (SrMV). A procedure was developed to assess the potential presence of potyviruses in a Poaceae‐infected sample, and then to determine which potyvirus species (one or more) were present. The first step was potyvirus‐group specific and following total RNA extraction, reverse transcription and polymerase chain reaction, it yielded a 327 nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
2
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 0 publications
0
29
2
2
Order By: Relevance
“…However, the cutting pattern by other enzymes are similar with a sequence similarities of 98.4-99.5% (nt) and 97.0-99.0% (aa) in the core region, thereby possibly representing the variant, SCMV-IND-CS. Since, single base mutation is sufficient for an isolate to lose a restriction site and to hamper typing by restriction[42].Although the isolates CB44-101, CBC92061-1, CBC92061-2, CB1148, and CB617, have deletions of 18 aa, the latter isolate varied from other isolates by showing 94.2-94.6% (nt) and 90.8-91.3% (aa) sequence similarities at core region and 66.9-92.1% (nt) and 87.9-89.6% (aa) sequence similarities at hyper variable region, hence CB617 represent the variant SCMV-IND-CO2. Moreover, it was not separated under any groups in both the phylograms and the cutting sites for all the enzymes are unique.…”
mentioning
confidence: 99%
“…However, the cutting pattern by other enzymes are similar with a sequence similarities of 98.4-99.5% (nt) and 97.0-99.0% (aa) in the core region, thereby possibly representing the variant, SCMV-IND-CS. Since, single base mutation is sufficient for an isolate to lose a restriction site and to hamper typing by restriction[42].Although the isolates CB44-101, CBC92061-1, CBC92061-2, CB1148, and CB617, have deletions of 18 aa, the latter isolate varied from other isolates by showing 94.2-94.6% (nt) and 90.8-91.3% (aa) sequence similarities at core region and 66.9-92.1% (nt) and 87.9-89.6% (aa) sequence similarities at hyper variable region, hence CB617 represent the variant SCMV-IND-CO2. Moreover, it was not separated under any groups in both the phylograms and the cutting sites for all the enzymes are unique.…”
mentioning
confidence: 99%
“…Being a distinct potyvirus as reclassified by Shukla et al (1992) and differentiated by Marie-Jeanne et al (2000) from other Poaceae viruses with a PCR test, JGMV was identified on maize samples in Turkey. This is the first report of the presence of JGMV in the Trakya region of Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Reaction mixtures were incubated at 42 °C for 50 min to synthesize the first strand cDNA, and then the reaction was inactivated by heating at 70 °C for 15 min. RT products were heated at 94 °C for 2 min and amplification was performed with 35 cycles of 30 sec for strand separation at 94 °C, 1 min for primer annealing at 50°C and 1 min for synthesis at 72 °C, and 10 min at 72 °C for final extension using pair of potyvirus specific degenerate primers (MJ1 and MJ2) (Marie-Jeanne et al, 2000).…”
Section: Methodsmentioning
confidence: 99%